2021
DOI: 10.1101/2021.12.03.471159
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Striatum-projecting prefrontal cortex neurons support working memory maintenance

Abstract: The medial prefrontal cortex (mPFC) and the dorsomedial striatum (dmStr) are linked to working memory (WM) but how striatum-projecting mPFC neurons contribute to WM encoding, maintenance, or retrieval remains unclear. Here, we probed mPFC→dmStr pathway function in freely-moving mice during a T-maze alternation test of spatial WM. Fiber photometry of GCaMP6m-labeled mPFC→dmStr projection neurons revealed strongest activity during the delay period that requires WM maintenance. Demonstrating causality, optogeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Previous studies suggested that the loops from the cortex through the basal ganglia could play a role in the maintenance of persistent activity for working memory (Wang, 2001; Wang et al, 2021). In accordance with this view, the nuclei of the basal ganglia are connected with frontal cortical regions that exhibit persistent activity during working-memory tasks (Saunders et al, 2015) and striatum-projecting neurons in the medial prefrontal cortex contribute to the maintenance of spatial working memories (Chernysheva et al, 2021). Furthermore, neurons of the basal ganglia themselves exhibit persistent activity during working memory tasks (Hikosaka and Wurtz, 1983; Hikosaka et al, 1989; Mushiake and Strick, 1995).…”
Section: Introductionmentioning
confidence: 77%
“…Previous studies suggested that the loops from the cortex through the basal ganglia could play a role in the maintenance of persistent activity for working memory (Wang, 2001; Wang et al, 2021). In accordance with this view, the nuclei of the basal ganglia are connected with frontal cortical regions that exhibit persistent activity during working-memory tasks (Saunders et al, 2015) and striatum-projecting neurons in the medial prefrontal cortex contribute to the maintenance of spatial working memories (Chernysheva et al, 2021). Furthermore, neurons of the basal ganglia themselves exhibit persistent activity during working memory tasks (Hikosaka and Wurtz, 1983; Hikosaka et al, 1989; Mushiake and Strick, 1995).…”
Section: Introductionmentioning
confidence: 77%
“…Furthermore, the DS is both directly and indirectly connected to the brain structures most implicated in cognitive and social function. For instance, inhibiting DMS-projecting mPFC neurons during the delay period of a T-maze working memory task impairs performance, and DMS neurons are sequentially active during this delay period (13, 38). The DS is also connected through basal ganglia outputs to the thalamocortical connections thought to sustain persistent activity in the PFC during delay periods of working memory (20, 39).…”
Section: Discussionmentioning
confidence: 99%
“…Wang, 2001;Wang et al, 2021). Consistent with this view, the nuclei of the basal ganglia are connected with frontal cortical regions that exhibit persistent activity during working-memory tasks(Saunders et al, 2015) and striatum-projecting neurons in the medial prefrontal cortex contribute to the maintenance of spatial working memories(Chernysheva et al, 2021). Furthermore, neurons of the basal ganglia themselves exhibit persistent activity during working memory tasks(Hikosaka and Wurtz, 1983;Hikosaka et al, 1989;Mushiake and Strick, 1995).On top of the anatomical organization, the basal ganglia contains separate pathways.The cerebral cortex projects to GABAergic neurons in the striatum that belong to the direct and indirect pathways (Figure 4.1B) and express different dopamine receptors.…”
mentioning
confidence: 70%
“…Consistent with torsion measurements in freely moving rats(Wallace et al, 2013), we found that torsion in mice was approximately linearly related to head pitch with a value of around 0.325 (FigureS2.8A).This value was used in all analyses.The distribution of left/right focea locations (Figure2.8B, FigureS2.8B) was computed using a grid of equally-spaced points in spherical coordinates (spacing 1°). The radius of the sphere was 10cm Ref 27. and the head of the animal was placed at the center of the sphere (nose pointing at ele=0° and azi=0°).…”
mentioning
confidence: 99%